2003
DOI: 10.1177/0022487102250310
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating The Use Of Group Interviews To Select Students Into Teacher-Education Programs

Abstract: This study presents findings on the reliability and validity of a group-assessment interview procedure designed to evaluate the verbal, interpersonal, and leadership qualities of students applying to a teacher-education program. We examine whether (a) the group-assessment process predicts future student-teaching performance, (b) the group-assessment scores are reliable across raters, and (c) the group-assessment interview is a better predictor of student-teaching performance than academic criteria. After gathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 18 publications
2
23
0
2
Order By: Relevance
“…The research conclusions outlined above are worth noting as they validate the hypotheses put forth by Shechtman (1989), Byrnes, Kiger, and Shechtman (2000) and Alem (2003) that certain personal abilities have a superior predictive value compared to cognitive abilities for explaining the success of interns during field placements. Shechtman and Godfried (1993) established the following three essential teaching competencies by conducting a factorial analysis of a set of 13 competencies deemed essential: (a) verbal communication, (b) interpersonal relations, and (c) sense of leadership.…”
supporting
confidence: 67%
“…The research conclusions outlined above are worth noting as they validate the hypotheses put forth by Shechtman (1989), Byrnes, Kiger, and Shechtman (2000) and Alem (2003) that certain personal abilities have a superior predictive value compared to cognitive abilities for explaining the success of interns during field placements. Shechtman and Godfried (1993) established the following three essential teaching competencies by conducting a factorial analysis of a set of 13 competencies deemed essential: (a) verbal communication, (b) interpersonal relations, and (c) sense of leadership.…”
supporting
confidence: 67%
“…These relationships were, however, found to be uneven: PPST and ACT scores appeared well-correlated with each other, but PPST scores were found to be weakly predictive of academic performance in teacher education programmes. In addition, the Byrnes et al (2003) study found the group-level assessment of teacher education students' verbal, interpersonal and leadership qualities to be more strongly predictive of teaching performance than were academic criteria. In essence, what these studies of teacher education students imply is that measures such as pre-admissions skills tests and tests of interpersonal qualities might be assessing generic or non-academic elements important in the selection of students, but that the consequential validity of these elements (whether they matter or are important) in relation to curriculum may need to be established.…”
Section: Introductionmentioning
confidence: 95%
“…Mikitovics & Crehan, 2002;Byrnes et al, 2003) have found associations between higher education academic performance and variables such as ACT scores, Pre-Professional Skills Test (PPST) scores, and student teaching ratings. These relationships were, however, found to be uneven: PPST and ACT scores appeared well-correlated with each other, but PPST scores were found to be weakly predictive of academic performance in teacher education programmes.…”
Section: Introductionmentioning
confidence: 99%
“…Byrnes, Kiger, and Shechtman (2003) contend that by emphasizing academic criteria, institutions overlook applicants' "verbal, interpersonal, and leadership qualities" (p. 163). Casey and Childs (2011) note that there is a relationship between applicants' academic averages and their success in teacher education programs, but caution that this relationship may be limited to the academic portions of these programs.…”
Section: Academic Averagesmentioning
confidence: 99%